Single cell RNA-sequencing identified CCR7+/RELB+/IRF1+ T cell responding for juvenile idiopathic arthritis pathogenesis - He, Lewei; Gong, Xue; Guo, Hui; Zhou, Kaiyu; Lan, Yue; Lv, Mingyi; Liu, Xiaoliang; Lin, Sha; Hua, Yimin; Guo, Junling; Fan, Zhenxin; Li, Yifei (Frontiers in Immunology, 2025)
BackgroundTo further explore the disease heterogeneity of different subtypes of Juvenile idiopathic arthritis (JIA) and analyze their pathogenesis mechanisms.MethodThe single-cell RNA sequencing (scRNA-seq) analysis of peripheral blood mononuclear cells (PBMCs) was carried out to investigate the disease heterogeneity and molecular mechanisms of immune responses in immune cells in JIA.ResultIn our study, we provided a immunological landscape of HLA-B27-positive JIA and HLA-B27-negative JIA immune cells at single cell RNA-Seq resolution. We found a higher proportion of CCR7+/RELB+/IRF1+ triple positive T cells in the peripheral blood of patients with JIA, and such T cells were predominantly present in HLA-B27+ JIA patients. Furthermore, we hypothesized that CCR7+/RELB+/IRF1+ triple positive T cells were highly activated T cells capable of promoting the differentiation of osteoclasts by producing IL-17, thus causing damage to cartilage in HLA-B27+ JIA patients. Unlike JIA patients, CCR7+/RELB+/IRF1+ triple positive T cells were not found in the peripheral blood of pSS patients and SLE patients, moreover, T cells from pSS patients and SLE patients were less able to produce IL-17 than those from JIA patients.ConclusionOur study provided evidence of cellular and molecular levels of involvement in JIA pathogenesis and identified the critical roles for T cells in JIA pathogenesis. Furthermore, our results suggested that there were significant differences in T cell composition and gene expression between HLA-B27+ JIA patients and HLA-B27- JIA patients. Our findings indicated that CCR7+/RELB+/IRF1+ positive T cells could damage the cartilage of HLA-B27+ JIA by producing cytokines such as IL-17.